A review on microfluidic devices for separation of blood constituents. Issue 1 (March 2020) - Mateen, Syed Abdul; Bhole, Kiran S
Abstract: This paper presents review of microfluidic device used for extraction of red blood cell, white blood cell, and plasma from the whole blood sample. . Micro fluidic based cell separation has various advantages as it reduces sample size, faster sample processing, has more sensitivity and low device cost as compared to the conventional method of blood cell separation. Basically there are two techniques for blood separation using microfluidic device, one is called active separation and another is passive separation method. The review highlights various cell separation methods. We will also take review on microfluidic based blood cell separation techniques. Separation of blood cells helps in clinical diagnosis and therapeutic research.